Faecal calprotectin as a reliable screening biomarker in the patients with organic bowel diseases (Bangladesh Journal of Medical Microbiology, 2012)
Calprotectin is a calcium and zinc binding protein released from leucocytes, markedly elevated in organic bowel diseases (OBD). Faecal calprotectin (FC) is supposed to be a reliable biomarker to screen the suspected patients with OBD. This study was aimed to determine the role of FC level in screening the suspected OBD patients. It was carried out by measurement of FC using a commercially available ELISA kit among 50 patients with chronic diarrhoea for ? 6 weeks with or without other GIT symptoms who underwent colonoscopic evaluation (35 OBD patients and 15 disease control) and 12 healthy control. Significantly higher value (P